Microbial landscape and immune status in maxillary sinusitis of stomatogenic origin - I.V. Kovach; S.D. Varzhapetian; Kh.A. Bunyatyan; O.E. Reyzvikh; A.A. Babenya; T.V. Strogonova (Medičnì Perspektivi, 2021)
Oroanthral fistula (anastomosis) is an element preventing the restoration of homeostasis in the maxillary sinus due to the constant flow of microbes from the oral cavity. It is also contributes to frequent exacerbations of maxillary sinusitis. Saprophytic gram-positive cocci and fungi of the oral cavity are dominating representatives of the microbial flora in the maxillary sinus. As the result of research, we found that in the case of maxillary sinusitis with oroantral fistula fungi made up 25.0% of microbiota, gram-positive bacteria – 41.7%, gram-negative bacteria – 33.3%. Gram-positive cocci from the Staphylococcus genus (Staphylococcus aureus and Staphylococcus epidermidis) and fungi (Candida albicans) comprised the biggest proportion of microbial flora that 33.3% and 16.7%, respectively. Slightly decreased levels of monocytes in venous blood was noted in 69.2% of patients. The average value of total serum IgE in group with oroantal fistula was 226.2 (70.4) IU/ml, the result exceeded normal limits almost in 2.26 times. Large circulating immune complexes (CICs) were normal in all patients in the group with iatrogenic maxillary sinusitis. The average lavels of small size CICs was 170.2 (4.23) ОU, which is in 1.06 times higher the upper limit of the norm (160 ОU). Elevated levels of total Ig E in serum of patients with oroanthral fistula indicates allergic sensitization. The detection of increased levels of CICs with small and medium sizes in serum may indicate a susceptibility of this category of patients to the development of immunopathological reactions.